Design and Development of a Water Filling System Using An Arduino Mega 2560 Based on Flowmeter Sensor - Ahmad Ridlo Hanifudin Tahier; Wahyu Riandika; Dhani Nur Indra Syamputra (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2026)
The utilisation of automation technology is undergoing rapid proliferation in the industrial sector, including in the bottled drinking water industry. The objective of this study is to design and implement an automation system for filling bottled drinking water with a range of 30–330 millilitres using an Arduino Mega 2560 as the controller. The setpoint is determined by calibrating the pulse value obtained based on the time delay in filling volumes in multiples of 30 at values ranging from 30 to 330 millilitres. The accuracy value for volumes of 30 and 60 millilitres was found to be 99.3%, while volumes of 60-330 millilitres demonstrated an accuracy level of >99.6%. Subsequently, the system was integrated with a conveyor and E18-D80NK proximity sensor to detect bottles during the filling process, and a counter to enumerate the bottles post-water filling. Preliminary testing indicated that the system demonstrated a capacity for precise bottle filling, with an error margin of less than 1%. This finding suggests that the system exhibits a low level of inaccuracy and responsiveness.